Price of everything: the true cost of living - "Porter, Eduardo" (London, 2011)
An ingeniously thoughtful and provocative look at how people overlook and misunderstand the role prices play in their lives. Key Features Aimed squarely at readers of The Undercover Economist (150k pbs) and The Economic Naturalist (80k pbs) Like Malcolm Gladwell, James Surowiecki, Jonah Lehrer and Thomas Friedman, Eduardo Porter combines counterintuitive stories and psychological studies with practical information. Brilliant reviews and stunning new cover for the Windmill paperback About the Book: The Price of Everything: The True Cost of Living Why is a life saved from a terrorist attack worth two saved from a natural disaster? Why are women more valuable than ever? Why do Americans tip when Europeans don't? And how can orange juice be used to predict the weather? The Price of Everything starts with a simple premise: behind every decision we make lies a price, whether we're buying a cup of coffee, taking a new job, or deciding to become a parent. Prices are the invisible thread that connect and explain our society, culture, economy, successes and failures. Revealing connections that are ingenious and unexpected, Eduardo Porter shows just how fundamental the price of things, work, happiness, faith, family and the future are - both to our everyday lives and to civilisation as we know it. About the Author: Eduardo Porter Eduardo Porter writes about business and economics as a member of The New York Times' editorial board. He has also worked as a journalist in Mexico City, Tokyo, London, Sao Paolo, and Los Angeles. He was editor of the Brazilian Edition of America Econom?a and covered the Hispanic population in the United States for The Wall Street Journal. He lives in New York. Reviews 'Enthralling ...Everyone could learn something from this wise and clever book. I
Keywords: Economics